PEMAHAMAN KONSEP SIRATAL MUSTAQIM PADA SURAT AL-AN'AM AYAT 151-153: IMPLIKASI DALAM PENDIDIKAN KARAKTER - Faridhatul Jannah, Widya; Waharjani, Waharjani; Suyoto, Suyoto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Challenges in character formation in which children and adolescents are exposed to various negative influences from their surroundings, obscuring their understanding of right and wrong, as well as a lack of understanding of religious concepts and environmental influences that affect character application. The purpose of this study is to discuss the understanding of the concept of Siratal Mustaqim in Al-An'am verse 151-153 and its implications in character education. The prohibition of association with God, the prohibiting of disobedience to parents, and the ban on killing children for the sake of poverty are key to forming a moral and ethical character for students. Besides, the command to perfect the scale, to speak honestly, and to keep promises are also important aspects in the formation of a good character. Character education that matches the concept of Siratal Mustaqim has profound implications in shaping individuals who are moral, ethical, and fearful.